Associations between moral injury, PTSD clusters, and depression among Israeli veterans: a network approach - Yossi Levi-Belz (European Journal of Psychotraumatology, 2020)
Background: Moral Injury (MI) is one of the adverse consequences of combat. Following exposure to potentially morally injurious events (PMIEs)––events perceived as violations of deep moral beliefs by oneself or trusted individuals––a significant minority of veterans could develop posttraumatic stress disorder (PTSD) and depression. Objective: The current study represents the first attempt to apply a network analysis model to examine an exploratory empirical conceptualization of a network of PMIEs during military service, post-traumatic stress disorder (PTSD) symptom clusters, depression, and combat exposure among Israel Defence Forces veterans. Method: A volunteer sample of 191 Israeli combat veterans were recruited during 2017, and completed validated self-report questionnaires tapping PMIEs, PTSD, and depression in a cross-sectional design study. A regularized Gaussian graphical model was estimated. Results: Network analysis revealed strong bridge associations between the PTSD nodes and most of the PMIEs nodes. The nodes of PMIE-betrayal and PTSD negative alterations in cognitions and mood (NACM) symptom cluster were found to have a bridging function between other PMIEs and PTSD. Depression was found to be connected to most of the PMIEs and PTSD nodes. Conclusions: The study’s findings offer an overview of the complex relationships between PMIEs and PTSD clusters among Israeli veterans. PMIEs––notably, betrayal-based experiences––are related to PTSD clusters directly and through depressive symptoms. Some possible mechanisms for the links between PMIEs and PTSD and the clinical implications related to specific interventions are discussed.